The Determinants of Entry by Domestic and Foreign Enterprises in Canadian Manufacturing Industries: Some Comments and Empirical Results - Gorecki, Paul K. (The Review of Economics and Statistics, 1976)
Paul K. Gorecki, The Determinants of Entry by Domestic and Foreign Enterprises in Canadian Manufacturing Industries: Some Comments and Empirical Results, The Review of Economics and Statistics, Vol. 58, No. 4 (Nov., 1976), pp. 485-488